A Finite-Element-Simulation Workflow and First Results of the Aero- and Vibro-Acoustic Signature of an Enclosed Centrifugal Fan - Heidegger, Patrick; Czwielong, Felix; Schoder, Stefan; Becker, Stefan; Kaltenbacher, Manfred (SAE Technical Papers, 2024)
Centrifugal fans are applied in many industrial and civil applications, such as manufacturing processes and building HVAC systems. They can also be found in automotive applications. Noise-reduction measures for centrifugal fans are often challenging to establish, as acoustic performance may be considered a tertiary purchase criterion after energetic efficiency and price. Nonetheless, their versatile application raises the demand for noise control. In a low-Mach-number centrifugal fan, acoustic waves are predominantly excited by aerodynamic fluctuations in the flow field and transmit to the exterior via the housing and duct walls. The scientific literature documents numerous mechanisms that cause flow-induced sound generation, even though not all of them are considered well-understood. Numerical simulation methods are widely used to gather spatially high-resolved insights into physical fields. However, for a centrifugal fan, the numerical simulation of the coupled aero- and vibroacoustic sound emission faces several hurdles, including a tedious meshing procedure, rotating parts, and the disparity of physical scales that need to be resolved for the acoustic field, the flow field, and the mechanical field. This work thus suggests a hybrid workflow to simulate sound generation and the through-wall sound transmission of an enclosed centrifugal fan. The workflow is based on three consecutive simulation runs: 1) a finite-volume-based incompressible CFD simulation to determine the low-Mach-number flow field, 2) a finite-element-based computational aeroacoustic simulation to determine the in-duct sound field, and 3) a finite-element-based vibroacoustic simulation that solves for the direct-coupled mechanic-acoustic simulation to determine the through-wall sound transmission. Additionally, an exemplary simulation of a test fan is conducted and discussed.
CRIS-Team Scopus Importer:2024-07-12